New Species and Records of Lemophagus Townes, 1965 (Hymenoptera, Ichneumonidae, Campopleginae), from China - Yuanyuan Han; Chengxue Wei; Chong Liu; Yan Dong (Insects)
Campopleginae, the third largest subfamily of Ichneumonidae, has been one of the most investigated ichneumonids from the perspective of biological control. Despite their importance as potential biological control agents, species of campoplegine are among the most poorly studied insect groups. In this study, one new species of the genus Lemophagus Townes, 1965, Lemophagus nanus sp. nov., is described and illustrated. In addition, L. curtus and L. pulcher are recorded from China for the first time.